2018
DOI: 10.1371/journal.pone.0208656
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of spontaneously occurring canine mammary tumours: Insight into gene networks and pathways linked to cancer pathogenesis

Abstract: Spontaneously occurring canine mammary tumours (CMTs) are the most common neoplasms of unspayed female dogs leading to thrice higher mortality rates than human breast cancer. These are also attractive models for human breast cancer studies owing to clinical and molecular similarities. Thus, they are important candidates for biomarker studies and understanding cancer pathobiology. The study was designed to explore underlying molecular networks and pathways in CMTs for deciphering new prognostic factors and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 119 publications
(104 reference statements)
0
18
0
Order By: Relevance
“…ANXA2 is a member of the calcium-dependent phospholipid-binding protein family and is related to the smooth muscle contraction pathway (29,30). A previous study using Affinity Capture-MS showed that ANXA2 binds to myosin heavy chain 9 protein, which is one of the downstream proteins in the Rho GTPase regulatory pathway (31). Overexpression of RP11-531A24.3 suppressed ANXA2 expression at both mRNA and protein levels compared with controls (Fig.…”
Section: Rp11-531a243 Suppresses the Migration And Proliferationmentioning
confidence: 86%
“…ANXA2 is a member of the calcium-dependent phospholipid-binding protein family and is related to the smooth muscle contraction pathway (29,30). A previous study using Affinity Capture-MS showed that ANXA2 binds to myosin heavy chain 9 protein, which is one of the downstream proteins in the Rho GTPase regulatory pathway (31). Overexpression of RP11-531A24.3 suppressed ANXA2 expression at both mRNA and protein levels compared with controls (Fig.…”
Section: Rp11-531a243 Suppresses the Migration And Proliferationmentioning
confidence: 86%
“…For example, CDC73 is a tumor suppressor, which can prevent cells from growing and dividing too fast or uncontrolled, and is closely related to parathyroid carcinoma ( Cetani et al, 2019 ). CDC123 is a cell division cycle protein, and the regulatory effects of the entire cell cycle process can be stopped in one of the normal stages (G1, S, G2, M).CDC123 is highly expressed in choriocarcinoma ( Hussain et al, 2018 ). B4GALT1 is one of the seven β -1,4-galactosyltransferase (beta4galt) genes.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis case-control GWAS also revealed a candidate region on Chr 7, with a suggestive SNP within the Vasohibin 2 ( VASH2 ) gene. Among other functions, VASH2 has been reported to be involved in mammary tumour development in dogs [ 21 ] and to enhance angiogenesis in mice [ 22 ]. In a study on soft tissue gene expression in CHD, the biological function “angiogenesis” was enriched by differentially expressed genes between CHD affected and unaffected dogs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%